PENGARUH PROFITABILITAS TERHADAP FINANCIAL DISTRESS DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN FARMASI DI BEI TAHUN 2021-2023 - Siregar, Fachrul A; Deliyanti Simbolon; Fenny Afrida (Ekomania, 2024)
A company experiences financial difficulties when it is in the pre-bankruptcy or pre-liquidation stage of financial distress. This study aims to examine the relationship between financial ratios and financial distress, controlling for company size, and to draw empirical conclusions about this relationship. The financial statistics used include the Return on Assets (ROA) proxy for Profitability and the Natural Logarithm of Total Sales (TLS) proxy for Company Size. Participants in this research were pharmaceutical businesses listed on the Indonesia Stock Exchange between 2021 and 2023. The sample size was 11 companies, all of which met certain requirements. Moderated Regression Analysis was used to analyze the data. Based on research findings, pharmaceutical companies listed on the IDX in 2021–2023, as measured by Return on Assets, are less likely to experience Financial Difficulty. However, the relationship between Return on Assets and Financial Distress can be moderated by company size. It is hoped that future research will expand the criteria and scope to cover more industries in many ASEAN countries, or at least expand existing research in the infrastructure sector. Other financial ratio factors, such as activity and liquidity ratios, should also be included.